2016
DOI: 10.1039/c6ra14932d
|View full text |Cite
|
Sign up to set email alerts
|

Supranutritional dietary selenium induced hyperinsulinemia and dyslipidemia via affected expression of selenoprotein genes and insulin signal-related genes in broiler

Abstract: The purpose of this study was to investigate the effects of supranutritional selenium (Se) on the mRNA expression of selenoprotein genes and insulin signal-related genes in the liver, muscle and pancreas of the broiler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
4
15
0
1
Order By: Relevance
“…The results showed that low levels of Se supplementation in diet (0.15–0.30 ppm) could effectively enhance the mRNA level of GPX and SelW , but excessive concentrations of Se could decrease the expression (Figure e–f). These findings were in line with those expressions in rainbow trout (Wang et al, ) and chickens (Huang et al, ). Gu, Ream, and Whanger () found that Se supplementation had no effect on the transcription rate of SelW but could prolong the half‐life period and stabilize its mRNA.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that low levels of Se supplementation in diet (0.15–0.30 ppm) could effectively enhance the mRNA level of GPX and SelW , but excessive concentrations of Se could decrease the expression (Figure e–f). These findings were in line with those expressions in rainbow trout (Wang et al, ) and chickens (Huang et al, ). Gu, Ream, and Whanger () found that Se supplementation had no effect on the transcription rate of SelW but could prolong the half‐life period and stabilize its mRNA.…”
Section: Discussionsupporting
confidence: 90%
“…Dietary Se deficiency (< 0.02 mg Se/kg) elevated fasting plasma glucose and decreased plasma insulin in birds ( Table 2 ) while it exhibited no effects on fasting plasma glucose and insulin concentration in pigs [ 10 , 35 ] and rat dams [ 9 ] models. Selenium is involved in carbohydrate and lipid metabolism in animal [ 11 , 14 ] and high Se exposure is associated with increased plasma lipid levels [ 11 ]. In present study, dietary Se deficiency induced pancreatic atrophy was associated with hypoinsulinemic hyperglycemia, and chicken also exhibited lower plasma TG and TC concentrations ( Table 2 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Although its importance for the prevention of certain forms of diseases such as exudative diathesis and nutritional pancreatic atrophy in chicken [ 4 ], Keshan disease and muscular dystrophy in human [ 5 ], and muscle malnutrition in swine [ 6 ] has been well established, the association between Se and glucose metabolism remains unclear. Recent studies report that supranutritional Se intake is associated with development of insulin resistance and hyperinsulinemia, and the alteration in blood lipid profiles in human [ 7 , 8 ], rodent [ 9 ], pig [ 10 ] and chicken [ 11 ] models. However, a number of animal experiments and epidemiologic investigations have shown the correlation between Se deficiency and glucose or lipid metabolic impairment [ 4 , 12 ] and as insulin mimetic, Se can activate key proteins involved in the insulin signaling pathway and has an anti-diabetic effect [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using large numbers of chicks fed Se-deficient corn-soy diets did find significant decreases in growth in Sedeficient chicks supplemented with 1X to 5X the NRC chicken vitamin E requirement [60][61]; these studies reported that 7-9 selenotranscripts were significantly decreased by Se deficiency. Supernutritional Se supplementation studies in chicks fed corn-soy diets have reported that high dietary Se decreases [62] or increases growth [63] along with increasing expression of subsets of selenotranscripts. Our studies in the young chick [18] and turkey poult [7] only found significant changes in 8 and 4 selenoprotein transcripts out of 24, respectively, in the livers of birds fed Se-deficient torula yeast diets for 4 weeks.…”
Section: Vitamin Ementioning
confidence: 99%